Розробка універсальної мови комп'ютерного перекладу - Барсуков, Дмитро; Некрасов, Олексій; Шапкін, Олександр (Видавництво Національного університету «Львівська політехніка», 2009)
The goal of the current work is development of universal computer translation language. This language is syntax-based, and oriented on possibility of translation into any natural human language. The minimal element of language structure is word that defines single concept Words are organized into sentences. The language can be used in translation programs, search systems, etc.
Keywords: artifical language; universal language; computer translation; штучна мова; структура слова; структура словника